Sharing Demand Information with Retailer Under Upstream Competition - Jain, Aditya (Management Science, 2022)
We analyze demand information sharing collaboration between two manufacturers and a retailer under upstream competition. The manufacturers produce partially substitutable products, which are stocked by the retailer that sells them in the market characterized by random demand. The manufacturers are privately informed about uncertain demand and decide on whether to share this information with the retailer. We show that by not sharing information, a manufacturer ends up distorting its wholesale price upward to signal its private information to the retailer, and under upstream competition, this distortion is propagated to the competing manufacturer. Thus, although a manufacturer’s decision to not share information may benefit or hurt its own profit, this always benefits the competing manufacturer. Under low intensity of competition, signaling-driven distortions exacerbate double marginalization and hurt all parties, whereas under more intense competition, these distortions help manufacturers offset downward pressure on wholesale prices. Thus, in equilibrium similarly informed manufacturers share information in the former case but not in the latter case. Additionally, when manufacturers differ in their information accuracies, only the better-informed manufacturer shares information. The retailer always benefits from both manufacturers sharing information, and its benefits are larger when the better-informed manufacturer shares information. We show existence of a contracting mechanism the retailer can employ to enable information sharing. Finally, we analyze manufacturers’ information acquisition decisions and find that under competition, two manufacturers acquire minimal information so that they are better off not sharing information in the information sharing game. This paper was accepted by Vishal Gaur, operations management.